Existence and Properties of Radial Solutions of a Sub-linear Elliptic Equation (Journal of Partial Differential Equations, 2015)
A non lipschitzian nonlinear elliptic equation is reviewed and results of existence, uniqueness, positivity and classification are proved using direct methods derived from the equation.
Keywords: Nonlinear elliptic equations; nodal solutions; Sturmcomparison theorem; variational method